Trends in Self-inflicted Violence Reports among Lesbian, Gay, Bisexual, and Transgender (LGBT) People in Brazil (Research, Society and Development, 2024)
Introduction: Self-inflicted violence involves intentional acts of self-harm to alleviate mental tensions and stresses, often resulting from traumas and social pressures. Objective: To analyze the trend of notification rates of self-inflicted violence among LGBT individuals in different Federal Units (UFs) of Brazil from 2015 to 2021. Methods: Data were collected from the Notifiable Diseases Information System, considering gender identity and sexual orientation of individuals aged 10 years and older. Annual rates were calculated and analyzed using linear regression with Stata 14.0, and the Prais-Winsten method was used to analyze the trends in notification rates. Results: A total of 11,817 cases were documented during this period. Regional distribution revealed that the Southeast registered the highest number of occurrences (5,570 cases). The highest notification rate occurred in the South region in 2017 (2.8 cases per 100,000 inhabitants). In terms of percentage variation, there was an overall increase of 123.5% in violence notifications. The time series analysis revealed increasing trends in Sergipe (AIA = 51.0; 95% CI 16.0 – 98.0) and the Federal District (AIA = 35.0; 95% CI 2.0-78.0). Conclusion: The rates of self-inflicted violence among LGBT individuals present a stable trend but vary regionally, highlighting the need for inclusive public policies and holistic approaches to prevention and protection, considering the complexity of the scenario.